The Application of Numerical Simulation in Debris Flow Disaster Early Warning: A Case Study of Shiyang Gully, China - Hao Zheng; Lanlan Guo; Jifu Liu; Bin Chen; Lianyou Liu (Land)
This study explores the application of numerical simulation in debris flow disaster early warning, using the Shiyang Gully in China as a case study. Using both the HEC-HMS and FLO-2D, the 18 June 2017 debris flow event was reconstructed to analyze the impacts of cumulative rainfall, rainfall intensity, and rainfall range on debris flow hazards. Simulation results showed that cumulative rainfall exceeding 90 mm or rainfall intensity surpassing 200 mm/8 h significantly increases debris flow depth, impact force, and affected areas, leading to severe structural damage. Expanding the rainfall range to the entire basin further amplifies disaster risks, increasing both inundation depth and exposed elements. Based on these findings, a four-tier debris flow early warning system was developed: (1) blue (IV) warning for cumulative rainfall of up to and including 20 mm or intensity of 200 mm/24 h, indicating preparation and monitoring; (2) yellow (III) warning for rainfall exceeding 20 mm but below 60 mm, requiring enhanced inspections and safety measures; (3) orange (II) warning for rainfall between 60 and 90 mm or intensity of 200 mm/12 h, necessitating immediate evacuation preparations; and (4) red (I) warning for rainfall over 90 mm or intensity of 200 mm/8 h, demanding full evacuation and emergency responses. This study demonstrates the value of numerical simulation in refining early warning systems by integrating multi-scenario analyses of rainfall parameters. The proposed system offers scientific and practical insights for enhancing debris flow disaster management, particularly in small, high-risk watersheds, providing a framework for cross-regional disaster mitigation strategies.